Impact of Rural Development Scheme of Islami Bank Bangladesh Limited on Beneficiaries in Mymensingh Sadar Area - Jinan, T; Bashar, A; Jahan, N; Khanam, TS (Progressive Agriculture, 2013)
The present study was conducted to assess the impact of investment provided under Rural Development Scheme (RDS) of the Islami Bank Bangladesh Limited (IBBL) on the basis of using data collected from 25 respondents of each of group of investors, agriculture and business of the five selected villages in sadar upazila of Mymensingh district. Total household annual incomes were Tk. 59696 and Tk. 87332 respectively for the agriculture group and business group. The beneficiaries have increased their income (61 percent in agriculture sector and 89 percent in business sector) by using RDS credit. After joining the RDS, there was a remarkable improvement in the living standard of the participant households. Thirty one percent of total credit received from RDS was utilized for agricultural purposes, 53 percent for business purposes and 15 percent for family expenditure on an average. Recovery rate of the current credit was 100 percent. None of the respondents of the group was allowed to have new credit until preceding credit was paid back. The findings suggest that the monitoring mechanism should be improved so that clients do not utilize their invested money to any unproductive activities. It is also suggested that adequate size of the investment has to be provided to pursue income generating activities properly. DOI: http://dx.doi.org/10.3329/pa.v19i2.16963 Progress. Agric. 19(2): 205 - 215, 2008